The temporality effect in counterfactual thinking about what might have been - BYRNE, RUTH MARY JOSEPHINE (Psychonomic Society, 2000)
When people think about what might have been, they undo an outcome by changing events in regular ways. Suppose two contestants could win 1,000 Pounds if they picked the same color card; the first picks black, the second red, and they lose. The temporality effect refers to the tendency to think they would have won if the second player had picked black. Individuals also think that the second player will experience more guilt and be blamed more by the first. We report the results of five experiments that examine the nature of this effect. The first three experiments examine the temporality effect in scenarios in which the game is stopped after the first contestant's card selection because of a technical hitch, and then is restarted. When the first player picks a different card, the temporality effect is eliminated, for scenarios based on implicit and explicit negation and for good outcomes. When the first player picks the same card, the temporality effect occurs in each of these situations. The second two experiments show that it depends on the order of events in the world, not their descriptive order. It occurs for scenarios without preconceptions about normal descriptive order; it occurs whether the second event is mentioned in second place or first. The results are consistent with the idea that the temporality effect arises because the first event is presupposed and so it is immutable; and the elimination of the temporality effect arises because the availability of a counterfactual alternative to the first event creates an opposing tendency to mutate it. We sketch a putative account of these effects based on characteristics of the mental models people construct when they think counterfactually.
PUBLISHED
Keywords: Psychology